Interior plastering of Ottoman bath buildings. (December 2019) - İpekci, Emre and Uğurlu Sağın, Elif and Böke, Hasan
Abstract: Ottoman baths were peculiar buildings with their function in community life, architectural characteristics and material use. Their interior spaces were exposed to high humidity and temperatures that made the building structure vulnerable to physical, chemical, physicochemical and biological degradations. Plasters used on the interior wall surfaces were the most important agents to protect the structure from deterioration and provide durability. This study aims to exhibit the plaster characteristics of Çinili Bath in İstanbul which was an outstanding example of Ottoman baths and built by Great Architect Sinan. Basic physical properties, raw material compositions, mineralogical, microstructural and hydraulic properties of original brick-lime plasters called as horasan (khorasan) plasters used on the walls were determined by XRF, XRD, SEM-EDS and TGA. Multilayered plaster application together with the use of glazed tiles were observed on the wall surfaces of all interior spaces. The plasters were produced from pure lime and pozzolanic crushed brick or tile aggregates and hydraulic because of the pozzolanic properties of aggregates. They are stiff, compact and durable in hot and humid conditions of bath buildings due to their self-healing properties and the formation of calcium silicate hydrates and calcium aluminate hydrates at the lime-brick interfaces and in the pores of the pozzolanic brick aggregates by the reaction of lime. Characteristics of brick aggregates were compared with the construction bricks used in the building. Their chemical and mineralogical compositions revealed that the aggregates had not been produced from construction bricks. All the results indicated that brick-lime plasters were the most suitable materials for bath buildings to protect the structure from the effect of water.